Interleukin (IL)-33: New Therapeutic Target for Atopic Diseases - Takeshi Nabe (Elsevier, 2014)
Abstract.: Interleukin (IL)-33, a member of the IL-1 family of cytokines, is produced when epithelial and endothelial cells are exposed to stimuli. Hematopoietic cells such as macrophages also produce IL-33. IL-33 is considered to function as an 'alarmin', activating various immune cells through its receptor ST2, which leads to the production of various molecules. The IL-33-induced production of pro-inflammatory cytokines is a critical event that aggravates atopic diseases such as asthma, atopic dermatitis, and pollenosis and suggests that IL-33-blocking agents could represent new therapeutic drugs. The anti-IL-33 antibody was effective in allergic models, whereas the anti-ST2 antibody has yielded controversial results because soluble ST2 functions as a decoy receptor for IL-33. IL-33-mediated pulmonary inflammation may be glucocorticoid-resistant especially when other cytokines act synergistically. Anti-tumor necrosis factor (TNF)-α therapy may also be effective against IL-33-mediated diseases. ERK1/2 inhibitors have also been shown to suppress the production of IL-33. On the other hand, activation of β2-receptors enhanced the expression of IL-33 mRNA in dendritic cells by activating protein kinase A (PKA), suggesting that PKA inhibitors may be candidates for IL-33-blocking agents. The effects of IL-33-blocking agents on atopic diseases need to be pharmacologically assessed in experimental and clinical studies. Keywords:: Interleukin (IL)-33, atopic disease, glucocorticoid, anti-allergic drug, asthma